Impact of the COVID-19 pandemic on epidemiological and clinical characteristics of Mycoplasma pneumoniae pneumonia in children: a multicenter study from Hubei, China - Du, Hui; Li, Jun; Li, Xilin; Zhao, Junhua; Lu, Wei; Zhang, Qiong; Liu, Wenchun; Luo, Xinbing; Lu, Qiao; Hu, Sanhong; Ma, Jilong; He, Renzhong; et al. (Frontiers in Pediatrics, 2024)
Aims: To investigate the epidemiological and clinical characteristics of M. pneumoniae pneumonia (MPP) children in Hubei, China. Methods: 30923 pediatric inpatients diagnosed with community-acquired pneumonia (CAP) from 20 hospitals in Hubei province, China, were included from January 2021 to December 2022. The codetected pathogens of M. pneumoniae (MP) were investigated using targeted next-generation sequencing (tNGS) test, and 23S rRNA gene mutations were detected to assess the macrolide resistance. Results: MP infected 20.7% of CAP patients, with cough (96.59%) and fever (80.28%) prevalent. In children younger than 1, 1-2, 3-6, 7-12, and older than 12 years, the infection rates were 6.17%, 19.98%, 26.97%, 43.93%, and 2.95%, respectively. Among 1349 patients undergoing tNGS, the overall co-detection rate was 59.45%, with Streptococcus pneumoniae (29.30%), Haemophilus influenzae (23.57%), and Human rhinovirus (17.21%) being commonly co-detected pathogens. In 635 patients undergoing the 23S rRNA gene mutation test, 86.30% had positive mutations (A2063G -98.00%, A2064G -1.50%, A2067G -0.50%). Despite a significant age difference (P=0.037) between macrolide resistant MP (MRMP)and macrolide sensitive MP (MSMP) groups, there were no significant differences in symptoms, lab data, or disease severity. Conclusions: In Hubei province, the prevalence of MP exhibited consistent changed during the COVID-19 pandemic. MPP was prevalent year-round, particularly in summer and autumn, with school-age children being more susceptible. Co-detections of viruses and bacteria were frequent in MPP cases, and macrolide resistance exceeded 85%. Ongoing surveillance of MP in children is crucial for understanding the healthcare impact of MPP.